(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This is an autobiography of the struggle icon Philip Kgosana, who felt that his contribution to the liberation struggle ought to have catapulted his name into history, hence the chronicle of his personal experiences as a political activist. He considers himself as one of the unsung heroes of the black struggle against apartheid, despite being a victim of racial discrimination on various fronts. In the first chapter, he laments the appalling socio-economic conditions under which he lived in Makapanstad, how chief Makapan of the Bakgatla nation fought the Boers and the European settlers who were advancing from the Cape known as the Trekboers in 1854. This has inspired him to resist the injustices of the apartheid system which had polarised the South African nation along racial lines. His political activism was therefore premised on the plight of the black people of Azania.